Developing a dancer wellness program employing developmental evaluation - Clark, Terry; Gupta, Arun; Ho, Chester H. (Frontiers in Psychology, 2014)
Wellness programs are being increasingly employed with performing artists. Given their aim of reducing injuries, injury tracking is commonly employed as an outcome measure. Evaluating the development and process of a wellness program can also enhance its effectiveness. Developmental evaluation offers one methodological framework within which to conduct such investigations. This paper reports on a two year process involving feedback from professional ballet dancers, management and artistic staff, and healthcare providers at a ballet company in order to develop a dancer screening and wellness program. Following a consultation phase, an initial program comprised of an expanded medical team and annual injury prevention screen was proposed. Alongside implementation with 30 professional ballet dancers, formal and informal feedback was sought from stakeholders and members across all levels of the ballet company to facilitate ongoing development, evaluation, and revision of the wellness program. The use of a process informed by developmental evaluation helped identify strengths and limitations within the screening process. The collective expertise of the assessors was used to modify the components and process of the screen to strive for ecological appropriateness. The process also fostered buy-in from all involved. Participant feedback helped refine the medical team available to the dancers and influenced the treatment and referral pathways via which dancers are able to access each member of the medical team. Furthermore, reflective discussions with artistic and management staff brought to light potential interactions between repertoire programming, fitness, and injury patterns. This prompted a reconsideration of how artists are trained and supported. Evaluation methods that focus on experiences and insight gained during program development stand to result in more efficient screening programs and health promotion models and, ultimately, healthier performing artists.